Prevalence and antimicrobial susceptibility pattern of Vibrio cholerae isolates from cholera outbreak sites in Ethiopia - Abebaw Bitew; Aschalew Gelaw; Yitayih Wondimeneh; Zeleke Ayenew; Michael Getie; Wudu Tafere; Tsehaynesh Gebre-Eyesus; Marechign Yimer; Getachew Tesfaye Beyene; Molalegne Bitew; Takele Abayneh; Markos Abebe; et al. (BMC, 2024)
Abstract Background Cholera is an acute infectious disease caused by ingestion of contaminated food or water with Vibrio cholerae. Cholera remains a global threat to public health and an indicator of inequity and lack of social development. The aim of this study was to assess the prevalence and antimicrobial susceptibility pattern of V. cholerae from cholera outbreak sites in Ethiopia. Methods Across-sectional study was conducted from May 2022 to October 2023 across different regions in Ethiopia: Oromia National Regional State, Amhara National Regional State and Addis Ababa City Administration. A total of 415 fecal samples were collected from the three regions. Two milliliter fecal samples were collected from each study participants. The collected samples were cultured on Blood Agar, MacConkey Agar and Thiosulfate Citrate Bile Salt Sucrose Agar. A series of biochemical tests Oxidase test, String test, Motility, Indole, Citrate, Gas production, H2S production, Urease test were used to identify V. cholerae species. Both polyvalent and monovalent antisera were used for agglutination tests to identify and differentiate V. cholerae serogroup and serotypes. In addition, Kirby-Bauer Disk diffusion antibiotic susceptibility test method was done. Data were registered in epi-enfo version 7 and analyzed by Statistical Package for Social Science version 25. Descriptive statistics were used to determine the prevalence of Vibrio cholerae. Logistic regression model was fitted and p-value < 0.05 was considered as statically significant. Results The prevalence of V. cholerae in the fecal samples was 30.1%. Majority of the isolates were from Oromia National Regional State 43.2% (n = 54) followed by Amhara National Regional State 31.2% (n = 39) and Addis Ababa City Administration 25.6% (n = 32). Most of the V. cholerae isolates were O1 serogroups 90.4% (n = 113) and Ogawa serotypes 86.4% (n = 108). Majority of the isolates were susceptible to ciprofloxacin 100% (n = 125), tetracycline 72% (n = 90) and gentamycin 68% (n = 85). More than half of the isolates were resistant to trimethoprim-sulfamethoxazole 62.4% (n = 78) and ampicillin 56.8% (n = 71). In this study, participants unable to read and write were about four times more at risk for V. cholerae infection (AOR: 3.8, 95% CI: 1.07-13.33). In addition, consumption of river water were about three times more at risk for V. cholerae infection (AOR: 2.8, 95% CI: 1.08-7.08). Conclusion our study revealed a high prevalence of V. cholerae from fecal samples. The predominant serogroups and serotypes were O1 and Ogawa, respectively. Fortunately, the isolates showed susceptible to most tested antibiotics. Drinking water from river were the identified associated risk factor for V. cholerae infection. Protecting the community from drinking of river water and provision of safe and treated water could reduce cholera outbreaks in the study areas.